The war in the Ancient Greece: technical and social aspects - Fonseca Soares, Martinho Guilherme (Romanitas - Revista de Estudos Grecolatinos, 2020)
Book review of: SEARS, M. A. Understanding Greek warfare. London: Routledge, 2019. 235 p.